(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Diabetic complications, comorbidities, and cost of treatment affect the quality of life (QoL) of an individual. The QoL assessment is considered an important measure of outcome in chronic disease management. Diabetes is a chronic disease, and it could affect both health and quality of life (QOL). A lot of studies have reported some predictors of QOL of type 2 diabetes patients. While their results were not completely consistent. So the aim of our study was finding out the related factors (including characteristics related to the disease, life styles and mental health factors) of QOL of type 2 diabetes patients. Quality of life (QoL) is an important outcome measure to assess the diabetic care and is increasingly replacing the traditional indicators of health. Most frequently affected life domain was the freedom to eat. A positive correlation was observed between QoL and gender, age, domicile, education status, occupation, family structure, duration of type 2 DM, HbA1c, insulin treatment, and the presence of comorbidities. The study highlights the impact of type 2 DM on QoL. Improving QoL of type 2 diabetic patients is important and knowledge of these preventable risk factors help to implement strategies to better management of type 2 DM and ultimately improve therapeutic outcome.